Surface‐Modified TiO2 Photocatalysts Prepared by a Photosynthetic Route: Mechanism, Enhancement, and Limits. Issue 1 (11th December 2013) - Neubert, Susann; Ramakrishnan, Ayyappan; Strunk, Jennifer; Shi, Haoyu; Mei, Bastian; Wang, Lidong; Bledowski, Michal; Guschin, Dmitrii A.; Kauer, Max; Wang, Yuemin; Muhler, Martin; Beranek, Radim
Abstract Surface‐modified TiO2 photocatalysts were synthesized by a photosynthetic route involving visible‐light‐induced (λ>455 nm) activation of benzene and toluene at the surface of TiO2 leading to the formation of carbonaceous polymeric deposits. IR spectroscopic and photoelectrochemical experiments showed that the mechanism of the photosynthetic reactions involves intra‐bandgap surface states at TiO2 related to surface OH groups interacting with adsorbed aromatic molecules. The photosynthesized surface‐modified TiO2 materials exhibited enhanced activity, relative to pristine TiO2, in photocatalytic degradation (and complete mineralization) of 4‐chlorophenol. The improvement was pronounced particularly under visible‐light (λ>455 nm) irradiation with the relative initial photodegradation rate enhanced by a factor of four. The surface‐modified photocatalysts exhibited good stability under the operating conditions, and the optimum carbon content was approximately 0.5 wt %. Mechanistic studies showed that the enhanced visible‐light photodegradation of 4‐chlorophenol is due to modified surface‐adsorption properties that facilitate formation of a surface complex between titania and 4‐chlorophenol, rather than due to any sensitizing effect of the carbonaceous deposits. The study highlights the importance of considering the interaction between pollutant molecules and the photocatalyst surface in heterogeneous photocatalysis, and possibly opens up a route for photosynthesis of further surface‐modified photocatalysts with tuned surface properties.